Utilización de un implante óseointegrado como anclaje para la retracción ortodóncica de un canino: estudio con elementos finitos - Vásquez-G., Mónica L.; Calao-Flórez, Eliana M.; Becerra-S., Fabio; Ossa-S., Jorge; Enríquez-G., Carlos; Fresneda-B., Eliseo (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The achievement of a proper intraoral orthodontic anchorage is very difficult or almost impossible, when the key teeth are missing. To achieve it, an anchorage unit, such as an endosseus implant, is mandatory, capable to withstand resistance to the forces exerted upon it, in order to get the movement of other teeth without anchorage displacement. In this study a tridimensional mathematical model was design, which includes an endosseus implant and an upper canine with its corresponding supports. Forces, moments and combined forces and moments were applied with a moment to force (M/F) ratio of 6.1:1, 10.3:1,13.9:1 and 26.4:1 to simulate canine retraction, with elastic chains and TMA (titanium - molybdenum) T loops of 0.017 x 0.025 inches. The finite element analysis calculated the strengths and movements of the proposed model, and the results showed a more uniform distribution with a lower magnitude of stress when a combination of force and moment were applied upon the model The point of greater stress was the cervical third of the implant and it’s surrounding bone, followed by the tooth; that acted as a rigid structure with a predominance of flexion, then the cortical bone and finally the periodontal ligament. The M/F ratio 6.1:1 showed a better stress distribution on the implant and the surrounding cortical bone, and the M/F ratio 10.3:1 showed the lowest stress and of a more uniform distribution for the tooth and the surrounding tissues. Based on these results, it can be suggested that when the anchbrage unit is a bone - integrated implant, it is better to use a calibrated retraction system without friction in which the M/F ratio is known.